Assessing the Effect of Dopants on the C−H Activation Activity of γ‐Al2O3 using First‐Principles Calculations. Issue 5 (30th November 2022) - Singh, Priti; Gogoi, Amrita; Aien, Qurat Ul; Dixit, Mudit
Abstract: In recent years, the high availability of methane in the shale gas reserves has raised significant interest in its conversion to high‐value chemicals but this process is still not commercially viable. Metal oxides, due to their surface heterogeneity and the presence of Lewis acidic and basic site pairs are known to facilitate the activation of C−H bonds of methane. In this work, we investigate the C−H bond activation of methane on pristine and doped γ‐Al2 O3 clusters using density functional theory (DFT) calculations. Our results demonstrate that the polar pathway is energetically preferred over the radical pathway on these systems. We found that the metal dopants (boron and gallium) not only alter the catalytic activity of dopant sites but this effect is more pronounced on some of the adjacent sites (non‐local). Among the selected dopants, gallium greatly improves the catalytic activity on most of the site pairs (including most active and least active) of pristine γ‐Al2 O3 . Additionally, we identified a correlation between H2 binding energies and the C−H activation free energies on Ga‐doped γ‐Al2 O3 . Abstract : The influence of neighbouring metal dopants (boron and gallium) in altering the catalytic activity of γ‐Al2 O3 is demonstrated using density functional calculations. Gallium greatly improves the catalytic activity of the material. A correlation between H2 binding energies and the C−H activation free energies is identified.